Group folklore and 'ideoculture' - Erdem, Servet (Millî folklor, 2012)
Having been employed for decades -from the beginning of the Folklore Studies as an academic field in the 19th century to the 1960s- to address communities that dwell in rural areas, and their cultural productions, the phenomena of `folk' and `folklore' had always been used in tandem with some assumptions and associations that were not free of certain pejorative implications such as illiteracy, rusticity, provinciality, peasantry etc. However, in the 1960s, Alan Dundes's redefinition of `folk' as `any group of people whatsoever who share at least one common linking factor' have revolutionized the trajectories of folkloristic research and caused a paradigm shift in the nature of folkloric subject. Hereby, over the past decades folklorists have been studying a wide variety of diverse groups and their cultural productions. However, these studies do not often completely break away from some parameters, definitions and research methods of the past century in which folklore studies were confined to only rural areas. This paper aims to discuss such negative ramifications in group culture studies and suggests an ideal model for them by briefly examining Gary Alan Fine's studies on the subject. Fine's conceptualizing of group culture and cultural elements which characterize an interacting group as the ideoculture seems to be one of the most effective suggestions have been put forward so far. Hence, it is argued that Fine's studies on ideoculture can be a model solution to the problems mentioned above. Reprinted by permission of Milli Folklor